Accelerating cosmologies of R4×Rᵐ1×Rᵐ2×Hᵐ3 type - Ch’ng, Han Siong; Zainuddin, Hishamuddin; Hassan, Zainul Abidin (2005)
In this paper, we study accelerating cosmologies resulting from compactifications of product internal spaces with time-varying volume. These internal spaces are taken to be the product of the flat space and negative curvature space. In this product case, there are more scalars and more complicated potentials and give the situation similar to the hybrid model of inflation.